(untitled) (Fiep Bulletin - online, 2013)
The process of manual digitization of anatomical points during the movement can generate error. The research aimed to analyze the variation in the digitization of the anatomical points intra and inter researchers during the movement of an adult. Participated in the study 1 subject with 20 years who received marks in the iliac crest, greater trochanter of the femur, femoral epicondyle, lateral malleolus and the fifth metatarsal. The subject walked in comfortable speed and was shot by a camera of 30Hz. 4 experienced researchers were selected to complete the process of digitization. Each one remarked through the software Degeeme v. 1.0, for 5 times the anatomical points of the right lower limb for the same subject’s step. For analysis was selected the point of the knee at 6 frames of a total of 38 who composed the step. The 6 tables are for the initial contact, the medium support, propulsion, initial balance, medium balance and final balance. Had been exported the coordinates "x" and "y" of the position of the knee point in each frame. The average, standard deviation and coefficient of variation were calculated from the five repetitions of each evaluator and among evaluators. The results show that the variation within researcher for the x axis was 0.1% to 0.5% and 0.1% to 0.7% for y axis. The researchers inter variation was 0.0% to 0.9% for x axis from 0.0% to 0.4% for y axis. The results of this study found that the researchers managed to reproduce the form shown markings, attesting to its accuracy. There also playing the scans between the different researchers, thus indicating the reliability of them.